Synthetic whole embryo models and their applications - Hanna, Jacob (Yaqub) (Henry Stewart Talks, 2022)
Differentiation, Early development, Ex utero growth, Gastrulation, Mouse embryo, Organogenesis, Research, Stem cells, Transplantation